AB1288 Method for automated, computer-based quantitative assessment of fluorescence optical imaging (FOI). (23rd January 2014) - Schirner, M.; Cziumplik, M.; Bahner, M.; Berger, J.
Abstract : Background: Diagnostic imaging, including ultrasound and MRI is routinely used in joint diseases. Besides initial diagnosis of the disease, imaging is also of strong interest for monitoring of treatment response. In this regard, semi-quantitative scores, like the RAMRIS or the US7 – score, aim at measuring disease activity. Most recently, fluorescence optical imaging (FOI) with the Xiralite® system became clinically available for diagnostic imaging of inflammation in the hands [1]. So far, a quantitative method for measuring disease activity has not been published. Objectives: We first report a method for an automated, computer-based algorithm for real-time, quantitative analysis of FOI images. Methods: 15 FOI standard exams were randomly selected from the multicenter OPERA1 trial (rheumatoid arthritis = 7; psoriatic arthritis = 8). These and 6 exams from normal individuals without clinical symptoms were calculated. Composite images of the first 240 seconds were generated. Using dedicated parameters of the histograms, automatic extraction of left and right hands from the image background was performed. After the extraction, the investigational algorithm separated the hands from the forearm in a standardized manner by using a multiple of the length of the middle finger. Next, a threshold in the fluorescence intensity curve was set to discriminate and measure high and low intensity areas in patients and healthy individuals. Next, high intensity areas of patients were compared with the mean value of normal individuals which was defined as reference value. D isease act ivity (DACT) is expressed as signal intensity (SI) (threshold to max patient /mean SI (threshold to max)healthy . DACT in healthy individual equals 1 which relates to an area of high intensity of 3.6%. Results: 21 left and 21 right hands were correctly extracted from the auto-scaled composite image of the first 240 seconds. The intra-individual variation of the extraction procedure measured as high intensity area in three consecutive procedures was <1%. The range of automatically calculated DACT values was 1.4–7.2 in RA patients and 1.6–10.3 in PsA patients. The mean DACT for the left and right hand was 3.7 and 4.1 in RA and 4.3 and 6.4 in PsA while the mean activity value for healthy individuals was 1. In a pilot case study a normal individual without clinical symptoms of arthritis received three consecutive examinations with the fluorescence agent indocyanine green (ICG) (0.05, 0.1 and 0.2 mg/kg body weight) in order to investigate the impact of varying ICG doses. The mean area of high intensity was 3.4% (2.9–3.7%; n=6) and was within the range of healthy individuals. Conclusions: Automatic, computer-based image analysis of FOI using dedicated software is technically feasible and offers high reproducibility. Measurement of areas of high signal intensity may provide a reliable quantitative readout for inflammatory activity. Varying doses of ICG do not have an obvious impact on auto-scaled composite images or calculated values. Further clinical investigations have to determine the agreement with other clinical measures (e.g. DAS28, ACR). References: Werner SG et al. Inflammation assessment in patients with arthritis using a novel in vivo fluorescence optical imaging technology. Ann Rheum Dis 2011: in press Disclosure of Interest: M. Schirner Shareholder of: mivenion, Employee of: mivenion, M. Cziumplik Employee of: mivenion, M. Bahner Shareholder of: mivenion, Employee of: mivenion, J. Berger Employee of: mivenion